If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4 = 13x + -6 Reorder the terms: 4 + 9x = 13x + -6 Reorder the terms: 4 + 9x = -6 + 13x Solving 4 + 9x = -6 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 4 + 9x + -13x = -6 + 13x + -13x Combine like terms: 9x + -13x = -4x 4 + -4x = -6 + 13x + -13x Combine like terms: 13x + -13x = 0 4 + -4x = -6 + 0 4 + -4x = -6 Add '-4' to each side of the equation. 4 + -4 + -4x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = -6 + -4 -4x = -6 + -4 Combine like terms: -6 + -4 = -10 -4x = -10 Divide each side by '-4'. x = 2.5 Simplifying x = 2.5
| (x*x)+3x+2= | | -1(y+3)=2 | | 10+z=3g | | p/4-(3p)/4=1-1/4 | | h(x)=x^2+6x-40 | | 9p-7q=-6 | | h(x)=x^2+23x-75 | | 7t+7=5t+11 | | 3(10)=9(3x-5) | | x=x-46 | | 4y+7+3y+10+y(-6)=256 | | -8u+6(6u)=22 | | 4a-7a=4 | | -36=-15-3x | | -7(2x+1)+3(5x+-4)=0 | | 2b+5i=12.9 | | 0.03x-2-1.2=0.24 | | 10+10+2x+15+3x-(-13)=-7 | | 7(2x+1)+3(5x-4)=0 | | 2z-6-5z=-24 | | 50=-6x+2(x+9) | | -51=-3x+2(-3x-3) | | ln(2*e)=x | | 6(4x+2)36=(3x) | | 10x+30=0 | | 2x+22=8-5x | | -6x+28=-8 | | 5y-3y-6=21.48 | | X^2+3x=16 | | 9x-10=170 | | 2x+3/2=18 | | 22-z=29 |